2003
DOI: 10.1590/s0004-282x2003000600021
|View full text |Cite
|
Sign up to set email alerts
|

Análise acústica da prosódia em mulheres com doença de Parkinson: comparação com controles normais

Abstract: RESUMO -Motivo do estudo:Alterações da voz, denominadas disartria hipocinética, têm sido bem caracterizadas em doença de Parkinson (DP), ocorrendo em 90% dos pacientes. No entanto, estudos da fala em DP, sobretudo em falantes nativos de outros idiomas que não o inglês são escassos. Nosso objetivo é comparar as características da prosódia de mulheres com DP com controles pareadas por idade, utilizando-se análise acústica. Método: Nós estudamos 8 mulheres com DP (68,4 ± 6,4 anos) e 8 mulheres controles (63,5 ± 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
10
0
9

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 6 publications
4
10
0
9
Order By: Relevance
“…These findings corroborate with other studies 10,17,22 that found lower amplitude of NT melodic variation in individuals with PD, giving speech a monotonous quality. The same stu dies show a lower rate of change of NT melodic variation in PD off compared with CG regarding the emission of short de clarative utterances.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These findings corroborate with other studies 10,17,22 that found lower amplitude of NT melodic variation in individuals with PD, giving speech a monotonous quality. The same stu dies show a lower rate of change of NT melodic variation in PD off compared with CG regarding the emission of short de clarative utterances.…”
Section: Discussionsupporting
confidence: 93%
“…Comparing PD off and PD on, only duration measure ments presented a statistically significant difference, show ing shorter duration in PD on, in agreement with the findings of other studies 16,17 . It is believed that this is because levodo pa therapy attenuates bradykinesia, reducing the duration of speech segments during its period of action.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In SD physical concomitants are common during speech due to the effort made to speak and possibly due to an associated orofacial dystonia 17,18 . In dystonias secondary to subcortical brain injuries, muscle co-contractions frequently occur, i.e.…”
Section: Discussionmentioning
confidence: 99%